2015
DOI: 10.1142/s0218810415500252
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes Following Pilon Fractures of the Middle Phalanx Managed with the Ligamentotaxor External Fixator

Abstract: The outcomes seen support the use of the Ligamentotaxor in the management of middle phalanx intra-articular fractures. It is simple to apply, potentially avoids the secondary complications of open reduction and gives reproducible results. However judicious patient selection is advised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…However, as the pain level was very low, these osteoarthritic changes did not appear to be symptomatic. This emphasizes the findings of the previous studies which describe an ongoing articular PIP joint remodeling after the removal of the external fixator and no clear correlation to subsequent osteoarthritic changes [19,24,25]. The limitations of this study are its retrospective design, the short follow-up period, and the relatively small number of patients, in accordance with other studies.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, as the pain level was very low, these osteoarthritic changes did not appear to be symptomatic. This emphasizes the findings of the previous studies which describe an ongoing articular PIP joint remodeling after the removal of the external fixator and no clear correlation to subsequent osteoarthritic changes [19,24,25]. The limitations of this study are its retrospective design, the short follow-up period, and the relatively small number of patients, in accordance with other studies.…”
Section: Discussionsupporting
confidence: 74%
“…However, there seems to be no clear association between residual articular step offs and the extent of osteoarthritic changes. Several authors described a short-or long-term remodeling capacity of the injured PIP joint [19,24,25]. The present study cohort showed 12 PIP joints anatomically remodeled without any residual intraarticular step off at the time of final follow-up.…”
Section: Discussionmentioning
confidence: 48%
“…A total of 48 articles were included in the final review, 5-52 25 of which reported data on dynamic external fixation, 12 on open reduction, 6 on hemi-hamate arthroplasty, 4 on extension block pinning, and 3 on percutaneous fixation. Two studies reported data on more than one group.…”
Section: Resultsmentioning
confidence: 99%
“…The third point concerns the importance of observance to treatment and postoperative rehabilitation to which MacFarlane et al are attached. We do agree, because all the authors who have published on the Ligamentotaxor ® say the same thing and give specific instructions to patients just after release of anaesthesia (Colegate-Stone et al, 2015; Damert et al, 2013; Gillespie et al, 2012; Körting et al, 2009; Pélissier et al, 2015). Table 4 of the article is interesting, but it compared Ligamentotaxor ® with other techniques.…”
mentioning
confidence: 77%
“…As stated by the authors of the recent correspondence, our results compare favourably with other authors who have published using the same device. Colgate-Stone et al (2015) reported a mean proximal interphalangeal joint range of motion of 63° and a Quick-DASH score of 9.1 at final follow-up with 12 patients. Similarly, Damert et al (2013) reported a mean range of motion of 73° and final QuickDASH score of 14.6 points at a mean of 15 months.…”
mentioning
confidence: 99%